The Geochemical and Textural Transition between the Reef Package and its Hanging Wall, Stillwater Complex, Montana, USA. (21st June 2022) - Jenkins, M Christopher; Mungall, James E; Zientek, Michael L; Butak, Kevin; Corson, Sam; Holick, Paul; McKinley, Ryan; Lowers, Heather
Abstract: The highest grade Pd-Pt deposit on Earth, the J-M Reef, is hosted in coarse-grained to pegmatoidal cumulates called the Reef Package. Decades of mine development of the J-M Reef have revealed that a distinct discontinuity in rock fabric marks the top of the rock unit that hosts economic-grade sulfide mineralization. Mine geologists refer to this discontinuity as the hanging wall contact. This contact is the top of the Reef Package and is always locatable—either by the change in rock fabric or by distinctive hanging wall textures of silicate minerals—even when the reef sulfide mineralization is absent. This rather subtle textural feature is used reliably by mine geologists to follow the Reef during exploration and mine development. Although some high tenor sulfides (>1000 ppm Pd in 100% sulfide) are found sporadically in the hanging wall cumulates, these accumulations are too small to be economically viable. We present quantitative rock fabric data for four Reef Package and hanging wall intersections collected by electron back-scattered diffraction (EBSD). Plagioclase fabrics in the hanging wall are characterized by low variance in grain sizes and a strong point maximum concentration of (010) and a perpendicular girdle distribution of [100] consistent with an axial B-type fabric. These fabrics are indicative of either compaction of the crystal mush or crystal settling of nucleated crystals, the bulk magma in a chamber. Conversely, the fabrics of the Reef Package show higher variance grain in size distributions and weak to undeveloped preferred orientation of plagioclase crystals that did not undergo significant alignment or textural equilibration of plagioclase grains. The absence of foliation in the Reef Package stands in contrast both to hanging wall fabrics and to other reported EBSD datasets of plagioclase crystals orientations from the Bushveld Complex, the Skaergaard Intrusion, and the Rum Intrusion. Furthermore, plagioclase crystal size distributions for the Reef Package show flatter slopes and convex profiles with fewer crystals at small size fractions indicating the dissolution of small crystals during partial melting and textural coarsening (i.e . Ostwald ripening) and crystal growth. Crystal growth was favored over the nucleation of new crystals during prolonged interaction with a hot infiltrating melt into the resident mush resulting in the coarse-grained textures of the Reef Package cumulates. The hanging wall contact represents a boundary between partially remelted crystal mush of the Reef Package, where sulfide mineralization formed and accumulated, and an overlying essentially barren cumulate pile. The hanging wall cumulates formed following the cessation of footwall erosion and the resumption of crystal accumulation by normal magma chamber processes.